Pengaruh Pemberian Air Cucian Beras terhadap Pertumbuhan Tanaman Tomat (Solanum licopersicum) - Nurlia, Nurlia; Anggo, Sulasmi; Idayanti, Iin (Program Studi Pendidikan Biologi FKIP Uniiversitas Muhammadiyah Luwuk, 2022)
: Factors which influence growht of plants consist of two parts, they are internal factors and external factors. One of the external factors that affect plants growth is nutrients. rice washing waste contains many nutrients needed by plants, but not many people use it. The purpose of this study is to determine the effect of rice washing waste on the growth of tomato (Solanum licopercum.) This research is experimental design. There were independent variable and dependent variable. Rice washing waste was independent variable and growth of tomato plants (Solanum licopersicum) was dependent variable. The research design used a randomized block design (RBD) model with 3 treatments and 3 replications. Data collection techniques using observation and documentation. The data analysis technique used the ANOVA test. The result of this research shows that the implementation of rice washing waste did not signficantly influence the growth of tomato plants (Solanum licopersicum) with significance value > 0.05. Key words: rice washing waste, growth, tomato